El Processoner del Monestir de Santa Maria de l'Estany - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2013)
From the Augustinian canons Monastery of Santa Maria de lEstany, in Moianès, a Processionary has been preserved, probably written in the same monastery between 1350-1375. It is now the manuscript Vic, Bibl. Episc., ms. 118. It is very important because it allows the reconstruction of an ancient costumary of the monastery now lost, the disposition of the church altars constructed during the 13th and 14th centuries and because its rubrics allow to propose that the monastic choir was placet in from of the main altar, on a high tribune as it was at Vic cathedral and the parish churches of Sant Andreu dOristà and Sant Andreu de Castellcir.